PENGARUH KETERSEDIAAN PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN OBAT-OBATAN PADA APOTEK KIMIA FARMA - Muhammad Rizki Aulia; Davin Salim (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2025)
The purpose of this study was to determine the effect of product availability and price on the decision to purchase medicines at Apotek Kimia Farma. This study used an associative research method with a quantitative approach. The sample in this study consisted of 100 respondents using accidental sampling. The data collection method was carried out by distributing questionnaires to the respondents. The results showed that the variables of product availability and price had an effect on the decision to purchase medicines at Apotek Kimia Farma. The test of the coefficient of determination () shows a value of 0.851, meaning that product availability and price have an 85.1% effect on the decision to purchase medicine at Apotek Kimia Farma, and 14.9% is influenced by other variables not examined in this study